SCREENING OF ORGANIC PREPARATIONS ON GROWTH AND VIABILITY OF THE SCLEROTIA OF VIABILITY OF THE SCLEROTIA OF VIABILITY OF THE SCLEROTIA OF Rhizoctonia solani Kuhn INVITRO AND IN SOIL - E. RAJESWARI; B. PADMODAYA; K. VISWANATH (The Bioscan, 2019)
The study was undertaken to screen the selected organic preparations under in vitro on mycelia growth and on the viability of the sclerotia of Rhizoctonia solani Kuhn causing sheath blight in rice soil. Among the five viz., cow urine, panchagavya, modified panchagavya, jeevamrutham and beejamrutham tested against sclerotial viability panchagavya and beejamrutham were found to be effective in inhibiting sclerotial germination even at lower incubation period of 6 h. While jeevamrutham and modified panchagavya inhibited sclerotial germination at higher incubation periods i. e., 18 h and 24 h. Panchagavya and jeevamrutham are found to be effective in inhibiting sclerotial germination in soil. Maximum mycelial growth inhibition by 100 percent was recorded with jeevamrutham and beejamrutham.